2022
DOI: 10.1101/2022.09.05.505575
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ChimeraTE: A pipeline to detect chimeric transcripts derived from genes and transposable elements

Abstract: Transposable elements (TEs) are structural variants considered an important source of genetic diversity, which may arise in the transcriptome when TEs are transcribed in the same RNA molecule as genes, producing what we hereafter call chimeric transcripts. The presence of chimeric transcripts has been associated with adaptive traits in several species, but their identification remains hindered due to the lack of tools to detect them on a transcriptome-wide scale. Previous bioinformatics tools were developed to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 130 publications
0
11
0
Order By: Relevance
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 2, 2022. ; https://doi.org/10.1101/2022.12.02.518890 doi: bioRxiv preprint and AS insertions group (911 vs. 61 insertions, respectively). Note that a recent analysis by Oliveira et al 43 also found this same region of the roo consensus sequence to be the most abundant in chimeric gene-TE transcripts across four D. melanogaster strains 43 . The authors evaluated whether these short sequences were widespread repeats across the genome.…”
Section: Chimeric Gene-te Transcripts Are Enriched For Retrotransposo...mentioning
confidence: 79%
See 2 more Smart Citations
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 2, 2022. ; https://doi.org/10.1101/2022.12.02.518890 doi: bioRxiv preprint and AS insertions group (911 vs. 61 insertions, respectively). Note that a recent analysis by Oliveira et al 43 also found this same region of the roo consensus sequence to be the most abundant in chimeric gene-TE transcripts across four D. melanogaster strains 43 . The authors evaluated whether these short sequences were widespread repeats across the genome.…”
Section: Chimeric Gene-te Transcripts Are Enriched For Retrotransposo...mentioning
confidence: 79%
“…This short roo sequence is more common in the internal insertions group than in the overlap and AS insertions group (911 vs. 61 insertions, respectively). Note that a recent analysis by Oliveira et al 43 also found this same region of the roo consensus sequence to be the most abundant in chimeric gene-TE transcripts across four D. melanogaster strains 43 . The authors evaluated whether these short sequences were widespread repeats across the genome.…”
Section: Chimeric Gene-te Transcripts Are Enriched For Retrotransposo...mentioning
confidence: 79%
See 1 more Smart Citation
“…We used TRF v. 4.09 (161) in all TE insertions from each genome, with parameters 2, 5, 6, 75, 20, 50, 500, -m, -h, and removed TEs that had SSRs over more than 50% of their sequences. Such method has been previously used to remove TE copies that are indistinguishable from simple repeats (34,162).…”
Section: Te Annotationmentioning
confidence: 99%
“…Exaptation and domestication events can be often identified by the occurrence of chimeric transcripts, which are mRNAs with both gene and TE-derived sequences (33). A recent transcriptome-wide study has identified that ~1.12% of D. melanogaster genes produce chimeric transcripts (34). Among all genes, 76 produce polymorphic chimeric transcripts from TE insertions that were present in one strain, but absent in another, highlighting the potential of TEs as a source of genetic novelty between different natural Drosophila ecotypes.…”
Section: Introductionmentioning
confidence: 99%